Microbiological Assessment of Groundnut (Arachis hypogaea L.) Sold for Consumption in Ghana - Felix Kwashie Madilo; Richard L. K. Glover; Md. Nazrul Islam; Nitai Roy; Emmanuel Letsyo (Journal of Food Quality, 2023)
The postharvest processes of groundnuts often become sources of microbial contamination leading to infections and intoxication. Hence, this study examined the microbial pathogens contaminating groundnuts after harvesting. About 50 samples were randomly collected from four major groundnut-producing towns: Bolgatanga, Chiana, Navrongo, and Bongo, all in the Upper East Region of Northern Ghana, and microbiologically examined using Analytical Profile Index (API® 20E). The results revealed that samples from Bolgatanga were the most contaminated, while Chiana has the least contaminated samples. Several species of bacterial genera such as Staphylococcus, Proteus, Escherichia, Bacillus, and Micrococcus, and fungal genera including Aspergillus, Fusarium, Rhizopus, Mucor, Saccharomyces, and Eurotium were isolated as the main microbial pathogens contaminating the produce. Navrongo and Bolgatanga recorded the highest rate of bacterial species for unshelled (29.5%) and shelled (30.4%) groundnuts, respectively, while Bongo and Bolgatanga registered the highest rate of fungal species under unshelled (32.8%) and shelled (32.6%) groundnuts, respectively. Due to the high levels of microbial contamination of most of the samples and the kind of microbial species involved, proper hygiene standards must be adopted during the postharvest handling of the shelled and unshelled groundnuts.